Pakistan : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
Pakistan's economy is at a critical juncture. Misaligned economic policies, including large fiscal deficits, loose monetary policy, and defense of an overvalued exchange rate, fueled consumption and short-term growth in recent years, but steadily eroded macroeconomic buffers, increased external and public debt, and depleted international reserves. Structural weaknesses remained largely unaddressed, including a chronically weak tax administration, a difficult business environment, inefficient and loss making SOEs, and low labor productivity amid a large informal economy. Without urgent policy action, economic and financial stability could be at risk, and growth prospects will be insufficient to meet the needs of a rapidly growing population.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet